Research of interdependence of trading partners countries macroeconomic indicators in conditions of economic integration (Journal of Economic Research & Business Administration, 2016)
The world experience of formation of various integration associations is analyzed. Studies in the EU show that European integration had a posi-tive effect on trade. The analysis of foreign and domestic literature on the impact of globalization and integration on inequality in income distribu-tion, the level and quality of life is carried out. Built in the current study the global model of vector autoregression involves major trade partners of Kazakhstan. As a result of model calculations derived functions of pulse impact - responses of all the variables for each country to various shocks such as a sharp drop in global oil prices, the growth of the real exchange rate in China, the decrease in production in Russia, and others are derived. On the basis of panel data econometric calculations and an estimate of the impact of globalization in the long run on income inequality and poverty in the three member countries of the EAEC Kazakhstan, Belarus and the Russian Federation have been conducted.
Keywords: economic integration; interdependence of indicators; modeling; socio-economic development.